Sinergi Pembelajaran Sosial-Emosional dan Teknologi AR dalam Penguatan Nilai Kewarganegaraan - Fara Diba Catur Putri (Journal of Humanities, Social Sciences, and Education, 2025)
The development of digital technology has presented new opportunities in education, including in strengthening civic values ​​in elementary schools. One relevant approach is social-emotional learning (SEL), which focuses on developing empathy, responsibility, and social awareness. The integration of Augmented Reality (AR) technology into this learning model is believed to increase student emotional and cognitive engagement through immersive and contextual learning experiences. This article is a literature review that aims to examine the synergistic role of social-emotional learning and AR technology in strengthening civic values ​​in elementary school students. Analysis was conducted on various national and international studies that highlight the effectiveness of AR in stimulating social interaction, value reflection, and active student participation in character-based learning. The study results indicate that the integration of AR and SEL can enrich the PPKn learning experience through visualization of social situations, empathy simulations, and collaborative activities that instill national values. In addition, AR technology also increases motivation and a sense of ownership of moral and social values. Thus, the synergy between social-emotional learning and AR has the potential to become a strategic innovation in civics (PPKn) education, helping to shape a young generation with character, empathy, and a strong sense of national awareness.